Baseline Survey and Needs Assessment of Sustainable Agricultural Mechanization in Ghana - Amankwaa-Yeboah, Patricia; Dalaa, Mustapha Alasan; Tepa-Yoto, Ghislain; Mkomwa, Saidi; Yeboah, Stephen; Kyere, Reginald; Obeng, Faustina; Adabah, Richard; Waldmann, Kaja; Mwika, Perseverance; Kariuki, Philip Wanjohi; Bourarach, El Hassane; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Sustainable agricultural mechanization holds great potential for addressing food security, poverty reduction and rural development challenges. This report compiles smallholder farmers’ needs, knowledge, and willingness to adopt and pay for sustainable agricultural mechanization (SAM) technologies and services in Ghana. The study was conducted in Offuman, an AICCRA intervention community under the pilot project “Go smart-mechanization! Increasing access to agricultural mechanization services in Ghana”. Results showed that extension officers (41%) and peer farmers and radio broadcasts (13%) were the major sources of agricultural information. Regarding mobile phone ownership, 86.5% of respondents owned mobile phone. Majority of respondents (94%) relied heavily on manual labor compared with mechanized farming. In terms of willingness to use a tractor service app, a majority of respondents, 62%, expressed willingness to use the app and pay. This indicates a positive attitude towards adopting technology for accessing tractor services. However, this positive attitude towards willingness to use the app is high among males (94%). Regarding capacity building in conservation agriculture (CA) and sustainable agriculture mechanization (SAM), 68% and 83% respectively reported that they have not received training, and the majority did not know the benefits of CA and SAM. These findings suggest that there is a need for increased capacity building and knowledge dissemination. The results indicate a very high willingness (97.0%) among the respondents to adopt and pay for SAM initiatives. These results suggest a favourable outlook toward adopting mechanized practices. In terms of potential financial sources for SAM activities, the majority of respondents, accounting for 53%, plan to rely on village savings and loans as their primary source of financing, indicating the need to strengthen local financial systems within the communities. The results provide valuable insights for policymakers, researchers, and development practitioners to formulate targeted interventions and strategies for promoting sustainable agricultural mechanization in Ghana and across Africa.